Follow-up of plasma semicarbazide-sensitive amine oxidase activity and retinopathy in Type 2 diabetes mellitus - Grönvall-Nordquist, Jenny L.E.; Bäcklund, Lars B.; Garpenstrand, Håkan; Ekblom, Jonas; Landin, Britta; Yu, Peter H.; Oreland, Lars; Rosenqvist, Urban (Journal of diabetes and its complications, 2001)
Plasma activity of the enzyme semicarbazide-sensitive amine oxidase (SSAO) is high in diabetes. Production of angiotoxic substances (an aldehyde, hydrogen peroxide, and ammonia) in vessel walls is catalysed by SSAO, suggesting a role for SSAO in the development of complications of diabetes. The objective of the present study was to follow up plasma SSAO activity (measured radiometrically), HbA 1c (using ion exchange chromatography), and retinopathy (by fundus photography) after 2.8 years, in 34 patients with Type 2 diabetes. We also measured urinary levels of an SSAO substrate, methylamine, by fluorometric high-performance liquid chromatography (HPLC). As at baseline, plasma SSAO activity was now higher in subjects with retinopathy (mean 19.5) than in subjects without retinopathy (mean 16.0), 95% confidence interval (CI) for difference 0.6–6.3 nmol benzylamine ml −1 plasma h −1. SSAO activity had not changed significantly since baseline, mean difference −1.65 and 95% CI for difference −3.76 to 0.46 nmol benzylamine ml −1 plasma h −1. Mean HbA 1c level remained higher for patients with retinopathy (now 7.9%) compared to those without retinopathy (6.1%), 95% CI for difference 0.6–3.0%. Comparing baseline and the present study, retinopathy was nonproliferative; level had worsened for five and improved for two patients. Urinary methylamine/creatinine ratio was lower in the group of patients with retinopathy (mean 0.99) than in those without retinopathy (mean 1.78), 95% CI for difference 0.1–1.5 μg mg −1. The results of the present study are compatible with a role for SSAO in the development of diabetic retinopathy.